STUDENT’S SELF CONCEPT OF DAYAK ETHNIC OF WEST BORNEO - Rizal, Yenni (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2016)
This  research purposes describing student’s self concept of Dayak ethnic of  West Borneo. The used instrument to identify concept of student self of Dayak ethnic is self’s concept scale that has been valid. This research subjects are 108 dayak students of threesenior high schools. The conducted research procedure is utilizing quantitative research - survey cross-sectional. Sample decision is chosen by convening sampling, that is chosen sample with ease consideration. The data analysis which resorted is percentage. Based on result of research finding, generally, describing student’s self-concept of Dayak ethnic is in very high category, includes perceptual aspect(physical self-concept),conceptual (psychologicalself-concept),and attitudinal. To summarize this research, students of dayak ethnic have very high category of self concept, however, if it is compared with five other ethnic at Pontianak, student’s self concept of Dayak ethnic of  West Borneo hold the worst result. Key words: Concept of Self, Dayak Ethnic Students.